1999
DOI: 10.1177/026765919901400105
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing liver blood flow after cardiopulmonary bypass: the effects of dopamine and dopexamine

Abstract: Liver blood flow is reduced after cardiopulmonary bypass (CPB) and both dopamine and dopexamine are used to overcome this. This study compares the effects of these agents on liver blood flow. Thirty patients undergoing elective coronary artery bypass graft surgery were randomized into three groups (n = 10 per group). Six hours after surgery baseline liver blood flow was determined by the percentage disappearance rate of indocyanine green measured by dichromatic auricular densitometery. Patients then received i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…14 It should be taken into account that mild impairment of liver function may already be present in cardiac surgical patients as a result of preexisting heart failure. 15 A possible explanation for the reduction in liver blood flow during hypothermic CPB might be a simultaneous loss of perfusion pressure. 14 Therefore, maintenance of a sufficient perfusion pressure during CPB should be of great interest, especially in patients with pre-existing organ impairment, endangered to develop severe postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…14 It should be taken into account that mild impairment of liver function may already be present in cardiac surgical patients as a result of preexisting heart failure. 15 A possible explanation for the reduction in liver blood flow during hypothermic CPB might be a simultaneous loss of perfusion pressure. 14 Therefore, maintenance of a sufficient perfusion pressure during CPB should be of great interest, especially in patients with pre-existing organ impairment, endangered to develop severe postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, the patients showed a rather high central venous pressure caused by the volume load and positive-pressure ventilation, and an elevation in venous pressure increases the extravasation of macromolecules. 22 Concerning dopamine, low-dose dopamine (4 µg • kg -1 • min -1 ) was demonstrated to enhance splanchnic blood, 23 and an increase in intestinal blood flow by isoproterenol was shown to increase the capillary filtration coefficient as a result of an increase in microvascular filtration area. 24 Accordingly, increased microvascular filtration can be assumed to occur during low-dose dopamine administration, at least in the splanchnic circulation.…”
Section: Baseline Disappearance Rate Of Albuminmentioning
confidence: 99%
“…A further three randomized controlled trials [28,53,54] concluded that dopexamine had no influence on pHi compared with dopamine or placebo. Dopexamine has also been shown to increase jejunal perfusion (as measured by laser Doppler flowmetry) and ICG dye clearance [55]. …”
Section: Resultsmentioning
confidence: 99%